2020
DOI: 10.3389/fphar.2020.00688
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Polypeptides as Significant Elastase Inhibitors

Abstract: Human neutrophil elastase (HNE) is a major cause of the destruction of tissues in cases of several different chronic andinflammatory diseases. Overexpression of the elastase enzyme plays a significant role in the pathogenesis of various diseases including chronic obstructive pulmonary disease (COPD), acute respiratory distress syndrome, rheumatoid arthritis, the rare disease cyclic hematopoiesis (or cyclic neutropenia), infections, sepsis, cystic fibrosis, myocardial ischemia/reperfusion injury and asthma, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 75 publications
1
18
0
1
Order By: Relevance
“…Indeed, the subsites S1 to S4 of the e cupied by the 2-amino-2-butenoic acid (Abu) and the N-terminal amino aci is similar to Tutuilamide B, except for the lack of an alanine residue and t an additional methylene in the side chain (Figure 5). Tutuilamides A-C ha for the inhibition activity against serine proteases, e.g., porcine pancreatic Tutuilamides A and B are the most active as inhibitors against PPE, with an Different peptides are produced by marine cyanobacteria belonging to genus Lyngbya [23]. Lyngbya confervoides coming from the Florida Atlantic coast is a producer of lyngbyastatin 4, a depsipeptide showing two peculiar residues of homotyrosine and Ahp; it has the ability to inhibit human neutrophil elastase, with an IC 50 value of 49 nM.…”
Section: Lyngbyastatin 4 and Lyngbyastatinmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the subsites S1 to S4 of the e cupied by the 2-amino-2-butenoic acid (Abu) and the N-terminal amino aci is similar to Tutuilamide B, except for the lack of an alanine residue and t an additional methylene in the side chain (Figure 5). Tutuilamides A-C ha for the inhibition activity against serine proteases, e.g., porcine pancreatic Tutuilamides A and B are the most active as inhibitors against PPE, with an Different peptides are produced by marine cyanobacteria belonging to genus Lyngbya [23]. Lyngbya confervoides coming from the Florida Atlantic coast is a producer of lyngbyastatin 4, a depsipeptide showing two peculiar residues of homotyrosine and Ahp; it has the ability to inhibit human neutrophil elastase, with an IC 50 value of 49 nM.…”
Section: Lyngbyastatin 4 and Lyngbyastatinmentioning
confidence: 99%
“…Eight cyclodepsipeptides have been produced by the filamentous fungi Beauveria felina after the addition of suberoylanilide hydroxamic acid (SAHA), a histone deacetylase (HDAC) inhibitor, to the culture medium; three of them are new compounds, e.g., desmethylisaridin C2, desmethylisaridin E and isaridin F [ 22 ]. This is an example of an epigenetic tool used for obtaining inhibitor peptides from fungal sources [ 23 ]. Among them, Desmethylisaridin C2, isaridin E, isaridin C2 and roseocardin ( Figure 3 ) are able to inhibit elastase release induced by formyl-L-methionyl-L-leucyl-L-phenylalanine (FMLP) in human neutrophils and to express an anti-inflammatory action without toxicity for human neutrophils.…”
Section: Natural Peptide Elastase Inhibitors Isolated From Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…8 Indeed, it has been shown that peptides derived from natural protein inhibitors are preferred over synthetic peptides as they cause less cytotoxicity. 9 Current natural inhibitor peptides, however, are unstable under pathophysiological conditions, show a lack of precise selectivity, and have an ineffective inhibitory potential. 2 Synthetic peptides with modified amino acids are therefore frequently sought and optimized to improve the affinity and inhibitory potential of peptides toward proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of the enzyme elastase assumes a huge part in the pathogenesis of different sicknesses including persistent obstructive pneumonic illness (COPD), intense respiratory pain condition, rheumatoid joint inflammation, the uncommon infection cyclic hematopoiesis (or cyclic neutropenia), sepsis, contaminations, cystic fibrosis, ischemia/reperfusion myocardial asthma, injury and irritation, and atherosclerosis [ 15 ] ; hence, study on drug or drug like molecules is important to explore a compound as potential candidate for its potency towards elastase inhibition or on the other hand for the disclosure of a chemical for treatments of different inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%